Inovasi Pembelajaran Mapel Matematika Dalam Kurikulum Merdeka Di MIN Kedungwuni - Amelia Novitasari; Fadila Ramadhania; Faris Maulana; Wildan Nur Nadhif (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to explore the effect of innovative mathematics learning in the Merdeka curriculum at MIN Kedungwuni. Using a literature study and interview approach, this research examines the perceptions and experiences of stakeholders, such as teachers, students and parents, related to the implementation of these innovations. The findings of this study are expected to provide insight into the effectiveness of mathematics learning innovations in increasing students' interest, conceptual understanding, critical thinking skills, collaboration, and mathematics achievement. The results of this study can provide a basis for further development in innovative mathematics learning in elementary schools